Increasing spin crossover cooperativity in 2D Hofmann-type materials with guest molecule removal. Issue 25 (6th June 2018) - Zenere, Katrina A.; Duyker, Samuel G.; Trzop, Elzbieta; Collet, Eric; Chan, Bun; Doheny, Patrick W.; Kepert, Cameron J.; Neville, Suzanne M.
Abstract : Ambient temperature spin crossover with wide hysteresis has been achieved in 2D Hofmann-type materials, where removal of guest molecules optimises ligand–ligand interactions, resulting in increased cooperativity. Abstract : Molecule-based spin state switching materials that display ambient temperature transitions with accompanying wide thermal hysteresis offer an opportunity for electronic switching, data storage, and optical technologies but are rare in existence. Here, we present the first 2D Hofmann-type materials to exhibit the elusive combination of ambient temperature spin crossover with wide thermal hysteresis (Δ T = 50 and 65 K). Combined structural, magnetic, spectroscopic, and theoretical analyses show that the highly cooperative transition behaviours of these layered materials arise due to strong host–host interactions in their interdigitated lattices, which optimises long-range communication pathways. With the presence of water molecules in the interlayer pore space in the hydrated phases, competing host–host and host–guest interactions occur, whilst water removal dramatically increases the framework cooperativity, thus affording systematic insight into the structural features that favour optimal spin crossover properties.